Reproducibility of cortical somatosensory evoked potentials in cross-country skiing: A proof-of-concept study - Piitulainen, H.; Giangrande, A.; Botter, A.; Cerone, G. L.; Karczewska-Lindinger, M.; Lindinger, S.; Piirainen, J. M. (10th International Congress on Science and Skiing, January 28 - February 1, 2025, Val di Fiemme, Italy, 2025)
INTRODUCTION: Skiing has positive effects on human health and motor ability in daily life activities [1-2]. However, the brain basis of skiing induced balance and motor control benefits are unclear. To unravel these mechanisms, the high quality and reproducibility of the electroencephalographic (EEG) signals recorded during skiing are prerequisite for longitudinal skiing studies. We examined the reproducibility of the skiing evoked cortical EEG potentials during cross-country skiing.